Skrining Fitokimia dan Karakterisasi Senyawa Metabolit Sekunder Ekstrak Daun Tumbuhan Niko (Grewia koordersiana Burret) - Landi Pote, Lodowik; Elisabeth Ipih, Hapat; Maximus M., Taek (Chemistry Department, Universitas Islam Indonesia, 2025)
Plants contain secondary metabolite compounds of flavonoid, alkaloid, tannin, saponin, triterpenoid and steroid groups. Therefore, this study needs to be conducted to determine the secondary metabolite compounds contained in the Niko plant (Grewia koordersiana Burret) and the characterization of secondary metabolite compounds of Niko plant leaf extract (G. koordersiana Burret). Sample preparation, maceration, chromatography fractionation and characterization with UV-vis spectrophotometer and infrared spectroscopy. The dried leaves were ground by blending and weighed 200 g of G. koordersiana Burret leaf powder sample and macerated with 1 L of methanol solvent for 48 hours, then filtered. Furthermore, the extract was evaporated by vacuum rotary evaporator at 45oC and waterbath. Furthermore, phytochemical tests were carried out on the extract and fractionation using column chromatography and characterization. The results of the phytochemical test showed that the extract contained flavonoids, steroids and saponins. The results of the fractionation of methanol extract of niko leaves with column chromatography with methanol-ethyl acetate-chloroform eluent (1:2:3) obtained 25 fractions. The fractions obtained were subjected to KTL with a ratio of methanol-ethyl acetate-chloroform eluent (0.5:5:3) and 20 fractions were obtained. Furthermore, 20 fractions were subjected to TLC with a ratio of methanol-chloroform eluent (0.5:3) and the fractions with Rf 0.3 were fractions 2, 7, 9, 16, 17, and 18. Fractions with the same Rf were combined and concentrated to obtain a thick extract. The results of the UV-Vis spectrum showed that there was a π→π* transition which was conjugated C=C, and the n-π* electron transition was the chromophore group C=O. The results of the FTIR spectrum show that the wave numbers 3360 cm-1 and 3334.92 cm-1 are the (-OH) group and the wave number 2945.3 cm-1 is the C-H group and the wave number 2833.43 cm-1 is the aliphatic C-H group and the wave number 1600 cm-1 is the aromatic C=C group and the wave number 1026.13 cm-1 is the alcohol C-O group.